Analisis Status Kualitas Air di Sungai Porong yang Tercemar oleh Deterjen terhadap Respon Hematologi Ikan Java Barb (Barbonymus gonionotus) - Nico Rahman Caesar; Uun Yanuhar; Abd. Rahem Faqih; Septi Anitasari; Gatot Ciptadi; Muhammad Musa; Mohammad Bisri; Muhammad Sumsanto; Nezya Pramudya Wardani (Postgraduate, University of Mataram, 2024)
The Porong River is one of the rivers that faces high anthropogenic impacts, such as surfactant waste from detergents. The hematology of Javanese carp (Barbonymus gonionotus) serves as a sentinel organism that can be used as a biomarker for the waters of the Porong River. The aim of this study is to analyze the water quality status of the Porong River polluted with surfactants using the STORET method, as well as its impact on the hematology of Javanese carp using regression and correlation analysis. The research employed a descriptive survey method. The results of the study indicated that the Porong River was categorized as moderately polluted. The average highest surfactant concentration reached 7.2 mg/L, leading to an increase in TSS to 107.95 mg/L and a decrease in DO to 1.80 mg/L. Surfactants exhibited a negative correlation with erythrocytes (91.2%), hematocrit (47.7%), and hemoglobin (60.6%), indicating that the higher the surfactant concentration, the lower the number of erythrocytes, hematocrit levels, and hemoglobin levels in Javanese carp. Conversely, there was a positive correlation between surfactants and leukocytes (56.7%) and blood glucose (66.7%), suggesting that the higher the surfactant concentration, the higher the number of leukocytes and blood glucose levels in Javanese carp.